Online Biodiversity Resources - Principles for Usability - Neale, Sophie; Pullan, M. R.; Watson, M. F. (Biodiversity Informatics, 2007)
Online biodiversity portals and databases enabling access to large volumes of biological information represent a potentially extensive set of resources for a variety of user groups. However, in order for these resources to live up to their promise they need to be both useful and easy to use. We discuss a number of principles for designing systems for usability, examine how these have been applied to the development of online biodiversity resources and compare this with a portal project developed by the Astrophysics community. We highlight a lack of user involvement and formalised requirements analysis by biodiversity projects resulting in a poor understanding of both the users and their tasks. We suggest a change in the way large biodiversity portal projects are structured, that is by providing infrastructure and supporting user groups developing individual interfaces.